DHA, EPA and their combination at various ratios differently modulated Aβ25-35-induced neurotoxicity in SH-SY5Y cells. (September 2018) - Zhang, Yong-Ping; Brown, Richard E.; Zhang, Ping-Cheng; Zhao, Yun-Tao; Ju, Xiang-Hong; Song, Cai
Abstract: Omega-3 polyunsaturated fatty acids ( n −3 PUFAs), docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), have been reported to prevent neurodegenerative diseases such as Alzheimer's disease (AD) in both experimental and clinical/epidemiological studies. However, whether DHA and EPA from natural products exert similar or different neuroprotective effects and how these n −3 PUFAs target cellular and molecular mechanisms associated with neurodegenerative disease pathogenesis are unknown. In the present study, we used amyloid-β (Aβ)25−35 -treated differentiated SH-SY5Y cells as a model of AD to compare the neuroprotective effect of DHA, EPA and their combination at various ratios. Administration of 20 μM Aβ25–35 significantly decreased SH-SY5Y cell viability, the expression of nerve growth factor (NGF), its TrkA receptor, and the level of glutathione (GSH) and increased reactive oxygen species (ROS), nitric oxide, tumor necrosis factor (TNF)-α, brain derived neurotrophic factor (BDNF) and its TrkB receptor. Aβ25–35 also increased the Bax/Bcl-2 ratio and the expression of Caspase-3 in these cells. Compared with the Aβ group, pretreatment with DHA/EPA significantly reduced cell death, especially at ratio of 1:1 and 2:1 DHA/EPA or pure DHA. However, the most efficient ratio for reducing changes in ROS and GSH and for decreasing TNF-α appeared at ratio of 1:2 and 1:1, respectively. The ratio of 1:1, 2:1 and pure DHA resulted in significant increase in the level of NGF. Furthermore, pure DHA was the most efficient for reducing Bax/Bcl ratio and Caspase-3 expression. In conclusion, DHA, EPA and their combination differently modulated Aβ25–35 -induced neurotoxicity in SH-SY5Y cells by exerting anti-oxidative, anti-inflammatory and neurotrophic effects. Highlights: DHA, EPA and their different ratios vary in their degree of protecting SH-SY5Y cells from Aβ25−35 insult. Pure EPA or higher ratio of EPA is more effective in anti-oxidative stress than DHA. DHA and EPA have distinct but synergistic anti-inflammatory effects in the cellular model of AD. Pure DHA or higher ratio of DHA is stronger to restore the changes in neurotrophin system induced by Aβ25−35. Both DHA and EPA attenuate apoptosis and improve cell viability, but DHA is more effective than EPA.